Human Herpesviruses HHV-6A, HHV-6B & HHV-7 : diagnosis and clinical management - Flamand, Louis (Burlington : Elsevier Science, 2014)
Completely revised and updated, Human Herpesviruses HHV-6A, HHV-6B & HHV-7, Third Edition, delivers a contemporary and thorough review of HHV-6, beginning with foundational explorations of classification, molecular biology, and chromosomal integration of the virus, through to clinical details, including pathologic features of infection, and clinical effects on various organ systems. The work now includes coverage of HHV-7, a virus that remains underestimated in transplant reactivation, seizures, and encephalitis. The work now includes coverage of HHV-7, a virus that remains underestimated in transplant reactivation, seizures, and encephalitis.
1. HHV-6A and HHV-6B officially as distinct viruses -- 2. Practical diagnostic procedures for HHV-6A, HHV-6B, and HHV-7 -- Pathologic features of HHV-6A, HHV-6B, and HHV-7 infection (light and electron microscopy) -- 4. HHV-6A, HHV-6B, and HHV-7 in febrile seizures and status epilepticus -- 5. HHV-6A, HHV-6B, and HHV-7 in encephalitis -- 6. Cognitive dysfunction from HHV-6A and HHV-B -- 7. HHV-6 and multiple sclerosis -- 8. Human herpes virus 6B in mesial temporal lobe epilepsy -- 9. HHV-6B and HHV-7 in exanthema subitum and related skin diseases -- 10. HHV-6A and HHV-6B in autoimmune disease -- 11. HHV-6A and HHV-6B in drug-induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms -- 12. HHV-6A and HHV-6B in solid organ transplantation -- 13. HHV-6A and HHV-6B in recipients of hematopoietic cell transplantation -- 14. The immune response to HHV-6 -- 15. Chromosomally integrated HHV-6 -- 16. HHV-6 and HHV-7 in cardiovascular disease and cardiomyopathies -- 17. HHV-6 in lymphohematopoietic diseases -- 18. HHV-6A and HHV-6B in cancer -- 19. Treating HHV-6 infections.
Print version record.
Keywords: Herpesvirus diseases; Herpesvirus diseases -- Diagnosis; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Herpesvirus diseases; Herpesviridae Infections; Electronic books